Asymmetric Au-catalyzed cycloisomerization of 1,6-enynes: An entry to bicyclo[4.1.0]heptene - Pradal, Alexandre; Chao, Chung-Meng; Toullec, Patrick Y.; Michelet, Véronique (Beilstein Journal of Organic Chemistry, 2011)
A comprehensive study on the asymmetric gold-catalyzed cycloisomerization reaction of heteroatom tethered 1,6-enynes is described. The cycloisomerization reactions were conducted in the presence of the chiral cationic Au(I) catalyst consisting of (R)-4-MeO-3,5-(t-Bu)2-MeOBIPHEP-(AuCl)2 complex and silver salts (AgOTf or AgNTf2) in toluene under mild conditions to afford functionalized bicyclo[4.1.0]heptene derivatives. The reaction conditions were found to be highly substrate-dependent, the best results being obtained in the case of oxygen-tethered enynes. The formation of bicyclic derivatives, including cyclopropyl pentasubstituted ones, was reported in moderate to good yields and in enantiomeric excesses up to 99%.
Keywords: asymmetric catalysis; bicycloheptene; cycloisomerization reactions; enynes; gold